Effect of Body Mass Index, Sputum Conversion Status, and Adverse Drug Events Severity On Health-Related Quality of Life of Drug-Resistant Tuberculosis Patients - Kurniawan, Sandy; Aphridasari, Jatu; Raharjo, A Farih (Indonesian Society of Respirology (ISR), 2025)
Background: Adherence to treatment guidelines and bacteriological conversion are the main indicators of successful treatment of drug-resistant tuberculosis patients. Evaluation of health-related quality of life (HRQoL) and the effect of treatment on HRQoL are often ignored. HRQoL assessment is an interesting outcome to evaluate and improve. Drug-resistant tuberculosis patients suffer not only from the disease but also from the effects of the treatment. Method: This study used a cross-sectional design to determine the correlation of body mass index (BMI), sputum conversion status, and adverse drug events severity with the HRQoL of drug-resistant tuberculosis patients. Quality of life assessment using the WHOQol-BREf questionnaire. The study was conducted in October 2022 at dr. Moewardi Hospital, Surakarta and Dr. Ario Wirawan, Salatiga. Determination of the sample by total sampling method. Results: HRQoL in 33 study subjects ie, 15 subjects had good HRQoL and 18 subjects had poor HRQoL. The media for each quality of life domain are the physical domain 43.00±6.20, psychological domain 33.21±8.83, social domain 28.21±11.01, and environmental domain 33.45±6.38. Statistical analysis with rank Spearman showed that there were a relationship between BMI (P=0.018), sputum conversion status (P=0.002), and adverse drug events severity (P=0.0001) with HRQoL of drug-resistant tuberculosis patients. Conclusion: BMI, sputum conversion status, and drug adverse events severity affect HRQoL of drug-resistant tuberculosis patients.